2012
DOI: 10.22495/cocv9i3art9
|View full text |Cite
|
Sign up to set email alerts
|

A study on Taiwanese corporate social responsibility and ownership structures

Abstract: This study develops several models to examine the relationship between the corporate social responsibility (CSR) and the ownership structure of Taiwanese firms. Our results suggest that firms which are controlled by professional managers, government-owned, or collectively-owned would like to undertake serious efforts to integrate the CSR into various aspects of their companies. Due to Asia firm’s culture, family firms might be more reluctant to put efforts on CSR activities. We also report that there is a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Finally, regarding Hypothesis 5, the study's findings are consistent with those from several previous studies (Lamb et al, 2017;Rees & Rodionova, 2015;Wu et al, 2012) that concluded that family directors are not important governance mechanisms and do not lead to a high level of CSR activities. However, Habbash (2016), Esa and Zahari (2016), and Liu et al (2017) found that family directors positively affect CSR disclosure.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, regarding Hypothesis 5, the study's findings are consistent with those from several previous studies (Lamb et al, 2017;Rees & Rodionova, 2015;Wu et al, 2012) that concluded that family directors are not important governance mechanisms and do not lead to a high level of CSR activities. However, Habbash (2016), Esa and Zahari (2016), and Liu et al (2017) found that family directors positively affect CSR disclosure.…”
Section: Resultssupporting
confidence: 89%
“…They explained that families disclose more CSR activities because they care about their names and reputations. However, some studies have asserted that family firms are controlled by large families' shareholders; they act for their benefit only and thus disclose fewer CSR activities (Rees & Rodionova, 2015;Wu et al, 2012). Meanwhile, Lamb et al (2017) found no significant relationship between family directors and information on CSR activities.…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…When engaging in CSR benefits society and deters families from pursuing their own benefits, families will engage in less CSR. Indeed, Wu et al (2012) argue that family firms are self-interested and undertake a lower level of CSR activities compared with non-family firms. Wu et al (2012) examine CSR practices in listed firms in Taiwan and find that family firms engage in less CSR.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Indeed, Wu et al (2012) argue that family firms are self-interested and undertake a lower level of CSR activities compared with non-family firms. Wu et al (2012) examine CSR practices in listed firms in Taiwan and find that family firms engage in less CSR. Similarly, Abdullah et al (2011) confirm the agency problem in family firms, which leads to a lower level of CSR activities and disclosures.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…On the other hand, authors have found that FFs show less engagement in CSR (e.g. Abdullah et al , 2011; Wu et al , 2012). Yet others have argued that FFs can be both socially responsible and irresponsible at the same time (Cruz et al , 2014), or that there are, for instance, no differences between FFs and NFFs in terms of their CSR policies (Amann et al , 2012).…”
Section: Introductionmentioning
confidence: 99%